PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN - SUGIYO PRANOTO, PAULUS (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract: Organizational culture becomes an identity of a company, with a good culture will have a positive impact employee performance. This applies also, when there is high motivation of employees in a company. High motivation of employees to improve employee performance. Research involving all employees of PT Crea Cipta Cemerlang with the number 80, by distributing questionnaires to 80 employees earlier. The sampling technique used was the study population and analyzed using SPSS version 16.0 with multiple linear regression method. The results show that the organizational culture and work motivation have simultaneously influence toward employee performance. Organizational culture and work motivation have a partial influence on the performance. Organizational culture becomes more dominant variable influencing employee performance than motivation variable. Keywords: organizational culture, motivation, and performance.